Bullying in Academic Medicine: Experiences of Women Physician Leaders. (20th January 2023) - Iyer, Maya S.; Way, David P.; MacDowell, Doug J.; Overholser, Barbara M.; Spector, Nancy D.; Jagsi, Reshma
Abstract : Purpose: Bullying is defined as offenders abusing positions of authority and intentionally targeting individuals through persistent negative behaviors to impede education or career growth. This study sought to estimate the prevalence and nature of bullying experienced by women physician leaders in academic medicine. Method: In this survey-based study, 547 physician graduates of an executive women's leadership training program were invited to complete a survey that measured workplace bullying in 2021. Participants were asked whether and when they had been bullied, how it impacted their careers, and remedies for bullying. Descriptive statistics were used to profile mistreatment and bullying experienced by the respondents during their professional careers and the nature of bullying. Content analysis of open-ended comments was used to describe how bullying impacted women physicians and outline recommendations for bullying prevention and mitigation. Results: The survey response rate was 64.7% (354/547). Most women (302/354 [85.3%]) had experienced mistreatment during their careers, with more than half experiencing bullying while an attending physician (198/302 [65.6%]). Many women (187/302 [61.9%]) who screened positive for mistreatment also reported that they had been bullied at work. Of these 187 respondents, 173 (92.5%) experienced bullying from men and 121 (64.7%) reporting bullying from women (effect size = 0.34, P ≤ .001), and 115 (61.5%) reported that bullies were their immediate supervisors. Qualitative findings suggested that bullying harmed individuals' career advancement, mental health, reputation, and relationships with others. Many had to change roles or leave jobs. Participants proposed that initiatives by top-level leaders, clear definitions of bullying behavior, reporting mechanisms, and upstander training for faculty and staff could mitigate bullying. Conclusions: Most women physician leaders have experienced bullying. These results highlight the need to address bullying in academic medicine so that women can reach their full career potential.